2009
DOI: 10.1039/b920833j
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Slovenian year 8 and year 9 elementary school pupils’ knowledge of electrolyte chemistry and their intrinsic motivation

Abstract: This study explored the differences between eight-year elementary school pupils (before the curriculum reform) and nine-year elementary school pupils (soon after the curriculum reform) in Slovenia, as regards specific chemistry knowledge and motivation to learn chemistry. Altogether, 191 elementary school pupils participated in the study. The results show that pupils of nine-year elementary school are not significantly better at chemistry knowledge test scores than eight-year elementary school pupils. Similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 30 publications
2
13
0
5
Order By: Relevance
“…These results are supported by this study, demonstrating not a strong but a negative relationship between students' amotivations levels and perceived academic achievement as it is expected. This finding was similar with the study of Jurisevic et al (2008), the results of which were related to the level of the pre-service primary school teachers' intrinsic motivation for learning science. The correlation between the level of motivation and the knowledge test results is not strong; nevertheless, it is statistically significant (Jurisevic et al, 2008).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These results are supported by this study, demonstrating not a strong but a negative relationship between students' amotivations levels and perceived academic achievement as it is expected. This finding was similar with the study of Jurisevic et al (2008), the results of which were related to the level of the pre-service primary school teachers' intrinsic motivation for learning science. The correlation between the level of motivation and the knowledge test results is not strong; nevertheless, it is statistically significant (Jurisevic et al, 2008).…”
Section: Discussionsupporting
confidence: 90%
“…This finding was similar with the study of Jurisevic et al (2008), the results of which were related to the level of the pre-service primary school teachers' intrinsic motivation for learning science. The correlation between the level of motivation and the knowledge test results is not strong; nevertheless, it is statistically significant (Jurisevic et al, 2008). On the other hand, Renchler (1992) examined academic achievement and motivation among American high-school students, who had A averages, and the results indicated that their level of motivation was not particularly high.…”
Section: Discussionsupporting
confidence: 90%
“…Ten of these reported connections (and sometimes significant correlations) between I/M/A and performance [147;157;176] or a few with self-concepts [28;40]. However, a small number of studies reported no connection between S&T achievement and perceived satisfaction [144] or 'internal motivation' [56]. Also, students selected to attend high-performing schools did not necessarily appear to have more interest in leisure activities in S&T [192].…”
Section: School-related Variablesmentioning
confidence: 99%
“…The students' inability to represent chemical phenomena at the sub-microscopic level can inhibit the ability to solve chemistry problems related to both macroscopic and symbolic phenomena (Chandrasegaran, Treagust, & Mocerino, 2007) ;Kozma, (2003). Other hand, the students were found difficulties in understanding the macroscopic representation into sub-microscopic and symbolic representations (Devetak, 2009;Davidowitz, et al, 2010). The difficulties faced by the students on the chemistry learning found when they combining the three level of chemical representations (Johnstone, 2000).…”
Section: Introductionmentioning
confidence: 99%